No goal is an island: the implications of systems theory for the Sustainable Development Goals - Skene, Keith R. (Environ Dev Sustain, 2020)
The Sustainable Development Goals (SDGs) have now been in place for 4 years, as the center-piece of the sustainable development program of the United Nations. This paper argues that the Earth system fundamentally represents the organizational framework of the planet and, therefore, any attempt at avoiding the existential threat to humanity that our activities are creating must be integrated within this system. We examine how complex systems function in order to identify the key characteristics that any sustainability policy must possess in order to deliver successful, long-term coexistence of humanity within the biosphere. We then examine what this means in terms of the SDGs, currently the dominant policy document on global sustainability and lying at the heart of Agenda 30. The paper explores what a sustainable program of actions, aimed at properly integrating within the Earth system, should look like, and what changes are needed if humanity is to address the multiple challenges facing us, based on systems theory. Central to this is the acknowledgement of shortcomings in current policy and the urgent need to address these in practice.